The Experience of Traumatic Father Loss in Late Adolescence and the Emotional Recovery Process - Kasenda, Rinna Yuanita; Carla Claudia Waleleng; Dinsiana Momongan; Dinda Mamonto; Ayu Ekaristi Br Ginting; Renita Hanaya Br Tarigan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The loss of a father during late adolescence often results in serious psychological trauma that disrupts emotional and social development. This study aimed to explore the traumatic experiences associated with father loss and the process of emotional recovery in late adolescents. Using a qualitative case study design, the population comprised late adolescents who experienced the sudden loss of a father, with a purposive sample of one participant who met the age and experiential criteria. The primary instrument was a semi-structured in-depth interview, which was analyzed using a descriptive qualitative approach through thematic coding and interpretation of subjective meanings. The findings revealed trauma symptoms such as flashbacks, trigger-related anxiety, concentration difficulties, and avoidance behaviors. Emotional recovery was supported by social support from a romantic partner and spiritual practices, particularly prayer. The conclusion emphasizes that the combination of these factors facilitates self-acceptance and emotional resilience, and it recommends holistic interventions in adolescent counseling.